Implementation of Project-Based Learning Model (PjBL) to Improve the Learning Outcomes of Social Studies Students - Ali Mashuri, Ali Mashuri; Taufiq Hidayat; Ali Noeruddin (Jurnal Pendidikan Edutama, 2025)
This study aims to improve social studies learning outcomes of grade VII students of Al-Kyai Sitiaji Junior High School, Sukosewu, Bojonegoro through the application of the Project-Based Learning (PjBL) model. The main problems identified were low student average scores and limited active participation during the learning process. This study uses Classroom Action Research (CAR) using the Kemmis and McTaggart models, which is conducted in two cycles. Data was collected through observation, documentation, and learning outcome tests. The results showed an increase in students' average scores from 65 to 75, and learning mastery increased from 47% to 82%. Student activity also increased, especially in terms of engagement during group discussions and project work. The implementation of PjBL has proven to be effective in improving learning outcomes and 21st century skills such as critical thinking, creativity, collaboration, and responsibility. This model can serve as an alternative to contextual and meaningful learning strategies in social studies education.